KORELASI PADA KARAKTER KOMPONEN HASIL TERHADAP HASIL KONSUMSI GALUR TANAMAN SAWI (Brassica juncea L.) - Novi Nurhalimah; Ngakan Made Adi Wedagama; Daniar Nastiti Ayunani; Devita Ari Safitri (AGRIMETA : Jurnal Pertanian Berbasis Keseimbangan Ekosistem, 2023)
Mustard is a type of horticultural vegetable that has nutrients and vitamins that are good for the body. Given the price of mustard which is quite economical in the community, many people consume these vegetables. The success of the effort to obtain mustard that have good quality and quantity of yield greatly supported by ability of plant breeders to obtain superior genotypes in selection stage. This research aims to find out correlation between yield components and yield on mustard. The next goal to find out character of yield components that have direct effect on the yield of mustard and can be used as basis for effective selection. The research was conducted in December 2018-March 2019 at Seed Bank and Nursery Agrotechno Park, BUA Universitas Brawijaya, located in Jatikerto Village, Kromengan District, Malang Regency, East Java Province. This research uses materials of 60 genotypes of mustard plants (Brassica juncea L.). The research method used randomized group design (RBD) expanded (augmented design). The treatments in study were arranged into 5 blocks and there were 60 experimental units each consisting of 7 plants. This research uses analysis of variance, covariance, and correlation with OPSTAT applications. The results of research showed that components of consumption yield were highly significantly correlated, including of leaf number, stem diameter, plant height and wet weight of harvest consumption weights. Plant height, stem diameter and wet weight can be used as an effective selection basis to decide consumption yield on mustard.